Oligosaccharide feed supplementation reduces plasma insulin in geldings with Equine Metabolic Syndrome - von Münchow, Alexandra; Torp Yttergren, Sarah; Jakobsen, Rasmus Riemer; Luthersson, Nanna; Hansen, Axel Kornerup; Lindenberg, Frederikke (Frontiers in Microbiomes, 2023)
Background: The prevalence of Equine Metabolic Syndrome and insulin dysregulation is increasing in the horse population. Insulin dysregulation is a risk factor for laminitis, which has significant welfare consequences for the horse. Current treatment strategies for Equine Metabolic Syndrome have variable effects on insulin sensitivity. Findings suggest that gut microbiota plays an important role in gastrointestinal barrier protection and metabolic diseases. Dietary supplementation with oligosaccharides has been shown to increase the production of short-chain fatty acids and induce changes in the gut microbiota, with an increase in insulin sensitivity. Objectives: We hypothesized that dietary oligosaccharide supplementation would ameliorate insulin dysregulation in horses with Equine Metabolic Syndrome. Study design: Fifteen horses were included in a cross-over study including two feed supplementations periods with oligosaccharide supplementation or calcium carbonate. Before and after each period plasma insulin, endotoxin, serum amyloid A, and blood glucose concentrations were measured during an oral sugar test and fecal samples were collected. Results: Oligosaccharide supplementation significantly reduced insulin in geldings (p = 0.02). Overall, none of the dominating bacterias changed significantly in relative -abundance. In the gut microbiota of mares, the Akkermansia genus and Clostridiaceae family were significantly more abundant. Within-sample bacterial diversity of horses with insulin concentrations > 60 mIU/L was significantly greater when compared to horses < 60 mIU/L. Horses with insulin concentrations > 60 mIU/L and horses with previous laminitis had a significantly greater beta diversity. Main limitations: Cut-off values for oligosaccharide feed supplementation/placebo dosing instead of dosing by g/kg body weight; owner compliance; single blood sample in oral sugar test; inter-horse variation Conclusions: This study demonstrated that oligosaccharide supplementation could improve insulin dysregulation in geldings with Equine Metabolic Syndrome suggesting that sex susceptibility might be a factor to consider. Additionally, a tendency of reduction of obesity-associated bacteria was observed. Furthermore, the diversity of the gut microbiota was significantly dependent on laminitis status and insulin concentrations. However, more studies on the effects of oligosaccharide supplementation on insulin dysregulation are needed to improve the dietary management of horses with Equine Metabolic Syndrome.